A beginner's guide to cryogenic electron microscopy. (1st April 2019) - Savva, Christos
Abstract : The 'Beginner's Guides' are a new ongoing series of feature articles in the magazine, each one covering a key technique and offering the scientifically literate, but not necessarily expert audience, a background briefing on the underlying science of a technique that is (or will be) widely used in molecular bioscience. The series will cover a mixture of techniques, including some that are well established amongst a subset of our readership but not necessarily familiar to those in different specialisms. Our first 'Beginner's Guides' covers cryogenic electron microscopy.